The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1590/s0101-81751999000400013
|View full text |Cite
|
Sign up to set email alerts
|

Descripción del sincraneo de Ameiva Ameiva (Linnaeus) (Squamata, Teiidae)

Abstract: ABSTRACT. Description ofthe syncranium of Ameiva Ameiva (Linnaeus) (Squamata, Teiidae). An osteological description ofthe syncranium and hyoid apparatus of Ameiva ameiva (Linnaeus, 1758) is presented. By comparison between males and females significant intersexual differences were found in relation to: skull size, frontal, parietal and basisphenoid bones, interptelygoid opening and teeth number and morphology. Absence ofpterygoid teeth in A. ameiva is verified out. The specimens used for this study carne from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 2 publications
0
17
0
4
Order By: Relevance
“…Post-cranial identification is based on the works of Etheridge (1967), Hoffstetter and Gasc (1969) and Lécuru (1968Lécuru ( , 1969. Several other works were used to specifically identify the Dactyloidae (Etheridge and De Queiroz, 1988;Etheridge, 1959;Frost and Etheridge, 1989;Nicholson et al, 2012;Poe, 1998Poe, , 2004, the Scincidae (Greer, 1970;Rao and Ramaswami, 1952) and the Teidae (Kosma, 2004;Pujos et al, 2009;Tedesco et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Post-cranial identification is based on the works of Etheridge (1967), Hoffstetter and Gasc (1969) and Lécuru (1968Lécuru ( , 1969. Several other works were used to specifically identify the Dactyloidae (Etheridge and De Queiroz, 1988;Etheridge, 1959;Frost and Etheridge, 1989;Nicholson et al, 2012;Poe, 1998Poe, , 2004, the Scincidae (Greer, 1970;Rao and Ramaswami, 1952) and the Teidae (Kosma, 2004;Pujos et al, 2009;Tedesco et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…, see also MacLean, ; Lopez and Cabrera, ; Montero et al, ; Rodrigues et al, ; Rodrigues et al, ; Tarazona et al, ; Gauthier et al, ). The Teiidae shows the same widespread condition of cercosaurines (Presch, ; Tedesco et al, ). Harris () described that in P. stenolepis the premaxilla does not contact the frontal, but we found that in some specimens of P. stenolepis , the premaxilla briefly contacts the medial process of the frontal bone, separating the nasals.…”
Section: Discussionmentioning
confidence: 79%
“…Because the suture between the prootic and otooccipital is completely fused, it was not possible to determine whether the anterior edge of fenestra ovalis is formed by the prootic, as has been considered by some authors for Tupinambis merianae (e.g., Barberena et al, 1970), for other Teiidae (Alvarez et al, 1987;Tedesco et al, 1999), and other lizards (Oelrich, 1956;Torres-Carvajal, 2002;Bell et al, 2003; Conrad, 2004;Bever et al, 2005). To clarify this point, it is necessary to examine specimens where the prootic/ opisthotic is still not fused but where the growth to this level has already ceased.…”
Section: Braincasementioning
confidence: 99%